Impact of and Reasons for Not Performing Exercise Training After an Acute Coronary Syndrome in the Setting of an Interdisciplinary Cardiac Rehabilitation Program: Results From a Risk-Op- Acute Coronary Syndrome Ambispective Registry - Cabrera-Aguilera, Ignacio; Ivern, Consolació; Badosa, Neus; Marco, Ester; Salas-Medina, Luís; Mojón, Diana; Vicente, Miren; Llagostera, Marc; Farré, Nuria; Ruiz-Bustillo, Sonia (Frontiers in Physiology, 2021)
Background and aims Exercise training (ET) is a critical component of cardiac rehabilitation (CR) that remains underused. The aim was to compare clinical outcomes between patients who completed ET (A-T), those who accepted but did not complete it (A-NT), and those who did not accept (R-NT), and to analyze reasons for not performing the ET component. Methods and results Unicenter ambispective observational registry of 497 patients with an acute coronary syndrome (ACS) carried out in Barcelona, Spain, from 2016-2019. The primary endpoint was a composite of all-cause mortality, hospitalization for ACS, or need of revascularization during follow-up. Multivariable analysis was carried out to identify variables independently associated with the primary outcome. Initially, 70% of patients accepted participating in the ET, but only 50.5% completed it. A-T group were younger and had fewer comorbidities. Baseline characteristics in A-NT and R-NT groups were very similar. The main reason for not starting or completing ET was rejection-reason unknown or work/schedule incompatibility. The median follow-up was 31 months. Both the composite primary endpoint and mortality were significantly lower in the A-T group compared to the A-NT and R-NT (primary endpoint: 3.6% vs. 23.2% vs. 20.4%, p<0.001, respectively; and mortality: 0.8% vs. 9.1% vs. 8.2%, p<0.001; respectively . In multivariable analysis, the only variables that remained statistically significant with the composite endpoint were ET completion, previous ACS, and anemia. Conclusions Completion of ET after an ACS was associated with an improved prognosis. Only half of the patients completed the ET program, with the leading reasons for not completing it being refusal-reason unknown and work/schedule incompatibility.. These results highlight the need to focus on the needs of the patients to guarantee that structural barriers to ET disappear.